Embedded Criticism Sebagai Cara Lain Menulis Kritik Seni Pertunjukan di Indonesia - Raditya, Michael Haryo Bagus (Institut Seni Indonesia Yogyakarta, 2023)
Embedded criticism as another way to write performing arts criticism in Indonesia. This paper performs a re-examining of performing arts criticism in Indonesia, particularly about a critic-artist relationship. The modern tradition of criticism has built a hierarchy in the performing arts ecosystem. It happened in any tradition of criticism and has been living in Indonesia for more than 50 years. Instead of it has lived in print media, for instance, newspapers and magazines, the relationship also happens on the Indonesian website. In fact, traditional performing arts in Indonesia were connected by a good relationship between a critic—for instance, a teacher or influential person—and an artist. It means the critic has access to watch a rehearsal, has a good chit-chat with an artist, can talk about the idea of the performance, and so on; it is not like the West critic, who was watching only the performance. The paper aims at presenting the other way of writing criticism, not only as an option of ways of writing but also providing the idea of a reciprocal relationship and renders less hierarchal the critic-artist relationship. As explained, this paper would like to discuss embedded criticism, the other way of criticism that attempted showing the relation between critic and artist as a productive work. Writing an embedded criticism describes a critic's duty that is not about judging the performance but also articulating the production and performance complexity. This paper would like to ask, how does critic presenting the criticism accommodates the relation between them? How can the embedded criticism apply to performing arts criticsm in Indonesia? Those questions will be answered by a literature study. The result of this research is that embedded criticism can be solved the gap problem of criticism—emphasizing the relationship between critic and artist in traditional performing arts, that undisclosed in the modern tradition of critic—through a website that disseminates performing art criticism.Tulisan ini mengkaji ulang kritik seni pertunjukan di Indonesia, khususnya tentang hubungan antara kritikus-seniman. Tradisi kritik modern telah membangun hierarki dalam ekosistem seni pertunjukan. Itu terjadi dalam tradisi kritik apa pun dan telah hidup di Indonesia selama lebih dari 50 tahun. Selain hidup di media cetak, misalnya koran dan majalah, yang cukup disayangkan hubungan itu juga terjadi di Indonesia melalui website seni. Padahal, seni pertunjukan tradisional di Indonesia dihubungkan oleh hubungan yang baik antara seorang kritikus—misalnya seorang guru atau orang berpengaruh—dan seorang seniman. Tidak seperti kritikus Barat, yang hanya menonton pertunjukan; tradisi kritik kita memiliki akses untuk menonton geladiresik, berbincang-bincang dengan artis secara akrab, dapat berbicara tentang ide pertunjukan, dan sebagainya. Atas dasar itu, tulisan ini bertujuan untuk menyajikan cara lain dalam menulis kritik, tetapi bukan hanya sebagai pilihan cara menulis melainkan juga memberikan gagasan tentang hubungan timbal balik dan memangkas hierarki antara kritikus-seniman. Seperti yang telah dijelaskan, tulisan ini hendak membahas embedded criticism atau kritik melekat, yaitu cara ungkap kritik yang berusaha menunjukkan hubungan antara kritikus dan seniman sebagai sebuah hal yang produktif. Menulis kritik melekat menunjukkan tugas seorang kritikus yang tidak hanya menilai ketika pertunjukan dihelat, tetapi juga mengartikulasikan kompleksitas produksi sekaligus pertunjukan. Tulisan ini memiliki dua pertanyaan, bagaimana kritikus menyampaikan kritik yang mengakomodasi relasi di antara kritik-pencipta karya? Bagaimana kritik melekat bisa diterapkan pada kritik seni pertunjukan di Indonesia? Pertanyaan-pertanyaan tersebut akan dijawab dengan studi literatur. Hasil dari penelitian ini adalah bahwa kritik melekat dapat memecahkan masalah kesenjangan kritik—menekankan hubungan antara kritikus dan seniman yang terjadi pada seni pertunjukan tradisional, yang tidak terungkap dalam kritik tradisi modern—melalui website yang menyebarkan kritik seni pertunjukan.